Sense of Purpose Among Female Students Belonging to Minority Ethnic and Buddhist Backgrounds. Issue 2 (3rd April 2018) - Sharma, Gitima; De Alba, Eva
Abstract: The present study explored sense of purpose among female college students belonging to minority ethnic and Buddhist backgrounds. The participants' experiences regarding the interpretation, role, and development of their sense of purpose were analyzed using a phenomenological approach. Participants defined purpose as their life's ultimate goal through which they aspired to contribute to world peace and happiness of all humanity. Having a sense of purpose strengthened their motivation, resilience, goal clarity, and ability to persevere. Several factors influenced participants' sense of purpose, including their cultural background, family history, personal hardships, spirituality, professional experiences, and altruistic endeavors. Implications of these findings in the context of research and practice are discussed.